(Smart CPS) Integrated application in intelligent production and logistics management: technical architectures concepts and business model analyses for the customised facial masks manufacturing. Issue 4 (4th May 2019) - Liu, Chang; Zhou, Yunzhu; Cen, Yutong; Lin, Dongtao
ABSTRACT: This research presents the technique architectures concepts and business model analyses for an innovative intelligent production model of facial masks, which consists of three modules: in-shop service, intelligent logistics, and smart manufacturing. The in-shop service module uses artificial intelligence to provide customers with quality experience. In the intelligent logistics module, the cyber-physical system (CPS) is used to conduct cloud processing of the traffic big data, aiming to provide an efficient intelligent logistics module for the transport of facial mask products to minimise transport time and costs. The entire process is highly efficient and fully intelligent in providing customers with customised facial mask production and services. As a result, it could be used by any Small and Medium Enterprises (SMEs) in this business and thus provides still another innovative application of smart CPS in production coordination and logistics management in the era of Industry 4.0 and Web 2.0.